Análisis a la información de costos y gastos generada en la sede Almacentro del Hospital Mental para determinar la rentabilidad obtenida (2011)
Mental Hospital of Antioquia, seeking to be more competitive in the marketplace, extended its coverage in the alternative site located in the Mall Almacentro, which provides outpatient services for Medical Specialist Psychiatrist, Medical subspecialists, Child Psychiatry, Outpatient by Medical Specialist Neurologist and outpatient drug market through the sale of pharmacy. Each business unit which makes up seat is making a number of costs that independently analyzed show a disproportionate distribution in relation to the generation of income. Currently the costs for outpatient services are not covered by income, only to consolidate the information casts reasonable results, to analyze the return produced. For the development of this paper we analyze the different components of the costs associated with the provision of outpatient services and sale of pharmaceutical products to determine the variables that affect the return in each business unit individually and consolidated headquarters Almacentro. The analysis was performed using spreadsheets, which were detailed in hospital costs for labor, supplies, overhead, distribution costs, among others, the collection of these data and the application of the linear estimation formula, we set the total variable and fixed costs, elements that allowed us to make the break-even analysis and contribution margin for the consultation service and product sales pharmaceutical required in the recovery of costs incurred and analysis generated in the consolidated return of information from headquarters.